Evaluation of plasma membrane integrity of frozen-thawed goat spermatozoa with or without seminal plasma - Azerêdo, G. A.; Esper, C. R.; Resende, Kleber Tomás de [UNESP] (Elsevier, 2001)
The aim of the present work was to evaluate plasma membrane integrity, motility, vigor and morphology of fresh and frozen goat spermatozoa with or without seminal plasma. Semen samples were diluted in Tris solution, before and after thawing, with a combination of carboxifluorescein diacetate and propidium iodide. The results showed differences (P < 0.01) for motility and minor defects in the presence or absence of seminal plasma, for both fresh and frozen samples. Periods of collection had a significant effect on motility, probably due to changes in the photoperiod. Plasma membrane integrity was significantly reduced by the freezing process, whether seminal plasma was present or absent. In conclusion, removal of seminal plasma decreased motility and vigor rates in frozen samples. The photoperiod probably decreased the testosterone level, contributing negatively to the high percentage of sperm abnormalities, mainly damaged membranes. The use of fluorescent probes allowed a better estimation of the percentage of functional cells, instead of only estimating the percentage of motile cells or morphology defects. © 2001 Elsevier Science B.V. All rights reserved.
Keywords: Cryopreservation; Fluorescent probes; Goat; Seminal plasma; Spermatozoa; Capra hircus